Systematic genome-wide and expression analysis of RNA-directed DNA methylation pathway genes in grapes predicts their involvement in multiple biological processes - Xiang, Rui; Ahmad, Bilal; Liang, Chen; Shi, Xiaoxin; Yang, Lili; Du, Guoqiang; Wang, Li (Frontiers in Plant Science, 2022)
RNA-directed DNA methylation (RdDM) is an important epigenetic pathway in plants and mediates transcriptional silencing by siRNAs. Different gene families have role in the regulation of the RdDM pathway and there is a lack of information about these gene families in the grapes (Vitis vinifera L.). Here, we mentioned the genome-wide identification, bioinformatics analysis, evolutionary history, and expression profiling of VvRdDM pathway genes against various stresses, hormonal treatments as well as in different organs. Sixty VvRdDM genes belonging to fourteen different families were identified. All the genes were unevenly distributed and chromosome 4 contained the highest number of genes (7). Most of the genes showed similar exon-intron and motif distribution patterns within the same subfamilies. Out of 14 families, only members of 4 families underwent duplication events during the evolutionary process and 50% of members of the AGO family are the result of duplication events. Based on Ka/Ks ratio all duplicated gene pairs have a negative mode of selection. VvRdDM pathway genes showed differential spatiotemporal expression patterns against different hormone and stress treatments. Further, with multiple transcriptome analysis, some VvRdDM genes showed a broad spectrum of high expression in different organs at various stages, and VvRdDM genes also displayed different expression in seeded and seedless cultivars during different phases of seed development. This proposed that VvRdDM genes may play multiple roles in grape growth and development, especially in seed development. qRT-PCR analysis of selected genes further verified the critical roles of RdDM genes in multiple biological processes, especially in seed development/ovule abortion i.e., VvIDN2a, VvDRD1a, VvRDR1a, and VvRDR6. Our study provides detailed information about VvRdDM genes in perspective of gene structure and evolution, as well as expression pattern against different stress, hormones and in different plants parts. It provides new candidate gene resources for further functional characterization and molecular breeding of grapes.